Maternal Knowledge of Pneumonia Care for Children Under 60 Months at the Pediatrics Department of Son Tay General Hospital in 2025 - Thi Minh Ngoc, Ha; Thi Hoa, Ho; Duc Anh, Ha; Thanh Hang, Phung (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
To assess maternal knowledge of pneumonia care for children under 60 months at the Pediatrics Department, Son Tay General Hospital, in 2025. Subjects and Methods: A cross-sectional descriptive study was conducted among 174 mothers whose children under 60 months were diagnosed with pneumonia and hospitalized at the Pediatrics Department, Son Tay General Hospital, from March to August 2025. Results: The mean score of basic knowledge about childhood pneumonia was 7.5 ± 2.7, with 56.3% of mothers demonstrating adequate knowledge. The mean score of care-related knowledge was 9.6 ± 3.1, with 75.3% scoring adequately. A significant positive correlation was found between basic knowledge and care-related knowledge, with a strong association (standardized β = 0.607; adjusted R² = 0.365; p < 0.001). Conclusion: Maternal knowledge of caring for children with pneumonia remains suboptimal. Strengthening health education to improve basic understanding of pneumonia may enhance mothers’ ability to provide appropriate care.